IJCM_400A: Perception towards family adoption programme among MBBS students of a medical college - A cross sectional study - Pramod; Basagoudar Shashidhar S.; Kirte Rahul C. (Wolters Kluwer Medknow Publications, 2024)
Background: National Medical Commission (NMC) in their recent notification included the Family Adoption Program (FAP) in the undergraduate medical curriculum to provide a learning opportunity towards community- based health care to Indian Medical Graduates. Notification documented that around 65.5 % of population resides in rural settings (as per 2020 statistics) whereas availability of health care facilities and services are skewed towards urban set ups. The student is expected to establish a rapport, understand their health and related factors, and help improve the healthcare of the family, by extensions, the community. FAP brings its challenges and opportunities. It is a very challenging task to implement programme by allotting families to each student and sustaining the follow up throughout the undergraduate period. Objective: 1. To assess the perception of students towards FAP. 2. To assess attitude of students towards FAP Methodology: Medical students who have completed their first year MBBS in RIMS, After obtaining informed oral consent, predesigned semi-structured questionnaire will be distributed to students who have completed their first year of MBBS Raichur will be included in the study. Students who are willing to participate in the study will be included in the study. Results: Will be presented in the conference. Conclusion: As this study aims to find the Perception of FAP for medical students, results of the study can be utilized to analyse the factors and take appropriate actions in the coming days.